2012
DOI: 10.1128/aac.05835-11
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem Resistance in Elizabethkingia meningoseptica Is Mediated by Metallo-β-Lactamase BlaB

Abstract: Elizabethkingia meningoseptica, a Gram-negative rod widely distributed in the environment, is resistant to most ␤-lactam antibiotics. Three bla genes have been identified in E. meningoseptica, coding for the extended-spectrum serine-␤-lactamase CME (class D) and two unrelated wide-spectrum metallo-␤-lactamases, BlaB (subclass B1) and GOB (subclass B3). E. meningoseptica is singular in being the only reported microorganism possessing two chromosomally encoded MBL genes. Real-time PCR and biochemical analysis de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 50 publications
0
58
0
1
Order By: Relevance
“…GOB is also peculiar in that its native organism, E. meningoseptica, is the only known bacterium expressing two MBLs: the B1 enzyme BlaB and the B3 enzyme GOB. We have shown that even if both genes are actively expressed, the higher levels of BlaB make this enzyme the one responsible for carbapenemase resistance (33). Thus, GOB could be redundant in this organism despite its efficient catalytic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GOB is also peculiar in that its native organism, E. meningoseptica, is the only known bacterium expressing two MBLs: the B1 enzyme BlaB and the B3 enzyme GOB. We have shown that even if both genes are actively expressed, the higher levels of BlaB make this enzyme the one responsible for carbapenemase resistance (33). Thus, GOB could be redundant in this organism despite its efficient catalytic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GOB enzymes present a divergent metal binding site with novel substrate binding features which make them unique among B3 MBLs. This observation, together with the finding that the resistance profile of E. meningoseptica is elicited mostly by the B1 enzyme BlaB (33), discloses a functional redundancy and suggests that GOB enzymes play alternative roles in this microorganism that have yet to be disclosed.…”
mentioning
confidence: 92%
“…(Docquier et al, 2002;Aubron et al, 2005;Girlich et al, 2010b;Henriques et al, 2012). Functional metagenomics studies have disclosed carbapenemase orthologs from bacteria in an Alaskan soil never inhabited by humans highlighting the huge pool of carbapenem resistance genes in the environment, which seems to predate the introduction of carbapenems in the therapeutic arsenal (Allen et al, 2009;Gonzalez and Vila, 2012). Environmental bacterial species carrying acquired CP genes have also been reported (Scotta et al, 2011).…”
Section: 72mentioning
confidence: 99%
“…In all previously reported clinical cases (6-8), E. anophelis isolates were resistant to most antibiotics recommended for empirical therapy, including third-generation cephalosporins, aminoglycosides and carbapenems (9), probably accounting for the poor infection outcomes. Consistently, most E. anophelis genomes harbor multiple antimicrobial resistance genes, including the two metallo-betalactamase genes bla GOB and bla blaB , associated with resistance to carbapenems (10). Currently, the clinical significance and biological distribution of E. anophelis is restricted, as this novel species is not well distinguished from other Elizabethkingia species in routine microbiological identification procedures, and as reference identification of E. anophelis relies mostly on the low-resolution 16S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%